Plant tissue culture as a tool for sustainable production of bentong ginger (Zingiber officinale var. Bentong) plantlets - M. Sundram, Tamil Chelvan; Khusairi, Ayadi M.; Zulkifli, Mazidah; Yunus, Muhamad Fahmi; Zainuddin, Zarina (2019)
Bentong ginger (Zingiber officinale var. Bentong) is an exotic ginger variety that can only be grown at highlands of Bentong district, Pahang, due to the fertile soil and cold temperate climate. Morphologically it has larger rhizome, thinner skin and contains less fibrous pulp compared to the domestic gingers. Besides, bentong ginger also has higher content of pharmaceutically important compounds (i.e. gingerol and shogaol) compared to other varieties of Malaysian gingers. However, cultivating this ginger through conventional agricultural practice has several constraints. Every season, almost 40% of the harvested rhizomes are set aside to be used as seeds for next cycle of cultivation. This has been a major drawback, hindering the continuous supply of ginger to fulfil the increasing market demand. Thus, in this final year project (FYP) research a systematic approach was taken to establish in vitro cultures of Bentong ginger plantlets. Prior to introduction into Murashige and Skoog (MS) media, young rhizome shoot bud explants were surface sterilised using different sterilization methods. Various responses were obtained from shoot bud explants cultured on MS basal medium supplemented with different concentrations of BAP and NAA; either alone or in combinations. Cultures were maintained under light condition 16 h/day photoperiod from white light of fluorescent lamps. In this preliminary study, augmentation of MS-medium with 3 mg/l BAP and with 1 mg/l NAA recorded the highest number of shootlets and roots multiplication. This in vitro regenerated Bentong ginger plantlets could serve the increasing needs of the planting materials for smallholder farmers. Indirectly, this could also improve the economic wellbeing of local farmers.